2023
DOI: 10.21608/menj.2023.284020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intradialytic Stretching Exercises on Muscle Cramps among Elderly Patients Undergoing Hemodialysis

Abstract: Background: Muscle cramps occur frequently among elderly hemodialysis patients, which can be avoided by the application of intradialytic stretching exercises. Purpose: Determine the effect of intradialytic stretching exercises on muscle cramps among elderly patients undergoing hemodialysis. Setting: The study was conducted at hemodialysis unit in Meet Khaqan Health Center affiliated to Shebin El-Koum Fever Hospital. Sample: The study subjects comprised of a convenience sample of 50 elderly patients who were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The previous study showed most of patients on hemodialysis had moderate level of leg muscle cramps(53%). 19 Another study stated that Almost 80% of patient undergoing Hemodialysis will experience leg muscle cramps, 36.6% were feel the muscle cramps at Sole. 20 Major consultations regarding muscle cramps were made to nephrologists and dialysis technician in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study showed most of patients on hemodialysis had moderate level of leg muscle cramps(53%). 19 Another study stated that Almost 80% of patient undergoing Hemodialysis will experience leg muscle cramps, 36.6% were feel the muscle cramps at Sole. 20 Major consultations regarding muscle cramps were made to nephrologists and dialysis technician in the study.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study among 90 patients on hemodialysis, it was found that stretching exercises had a positive effect on the reduction of restless leg syndrome [ 30 ]. Similarly, in a study of 50 elderly hemodialysis patients, there was a significant reduction in muscle cramps in participants who followed stretching exercises during hemodialysis [ 31 ].…”
Section: Reviewmentioning
confidence: 99%